Effectiveness Of Bundle Care In Preventing Pressure Ulcer In Patients Using Mechanical Ventilation Assistants In The Intensive Care Unit - Nurhusna; Oktarina, Yosi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background : The incidence of pressure sores (pressure ulcers) in the intensive care unit (ICU) is very high and many strategies have been implemented to overcome this problem. aim of study is to describe the implement of bundle care to prevent ulcers in the intensive care patients. Method : This is descriptive analytic research. Respondents were all nurses in the intensive care unit at the General hospital, Jambi Province, totaling 30 respondents. Monitoring the effectiveness of bundle care in patients who use mechanical ventilation devices who are treated in the ICU with a length of stay of >3 days. Results : This study has revealed the application of Bundle Care in preventing pressure ulcers by nurses in the ICU room for patients who use mechanical ventilation assistive devices shows that in general ICU nurses carry out 6 principles of bundle care such as risk assessment, skin assessment, skin care, repositioning, nutrition, maintenance of medical devices installed. Based on the table above, it is known that aspects of medical device care and nutrition are carried out in full (100%) Conclusion :generally nurses carry out skin assessments, skin care with a percentage range of 50-100%. However, it can be seen that repositioning activities are still carried out below 50%. Keywords: Bundle Care; Pressure Ulcer; Intensive Care